2015
DOI: 10.1016/j.jesf.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activation during push-ups performed under stable and unstable conditions

Abstract: Not all unstable devices enhance muscle activation compared to traditional push-ups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 15 publications
1
41
0
4
Order By: Relevance
“…such as 16 high school swimmers involved in 8 weeks of core training, the results show that the core training group in the explosive power project and the control group have significant differences [3]; The effect of the training of nuclear myocardium and the enhancement training on rugby players' special athletic performance found that core muscle group training can improve speed, explosive force, coordination and stability [4]. The effect of the 8-week core training on the students' vertical jumping and stability limit, the results show that the core training can improve the students' jumping performance [5].The effect of 8-week core training on the students' agility and jumping ability, the results show that the eight-week core training can improve the students' agility and jumping ability [6]. According to the above literatures and the research results of this study, it is possible to prove that TRX suspension training can be used to stabilize the core muscle group and to train the coordination of the whole body muscles in each training action.…”
Section: Results and Analysismentioning
confidence: 95%
“…such as 16 high school swimmers involved in 8 weeks of core training, the results show that the core training group in the explosive power project and the control group have significant differences [3]; The effect of the training of nuclear myocardium and the enhancement training on rugby players' special athletic performance found that core muscle group training can improve speed, explosive force, coordination and stability [4]. The effect of the 8-week core training on the students' vertical jumping and stability limit, the results show that the core training can improve the students' jumping performance [5].The effect of 8-week core training on the students' agility and jumping ability, the results show that the eight-week core training can improve the students' agility and jumping ability [6]. According to the above literatures and the research results of this study, it is possible to prove that TRX suspension training can be used to stabilize the core muscle group and to train the coordination of the whole body muscles in each training action.…”
Section: Results and Analysismentioning
confidence: 95%
“…Low High TRX ART c) Latissimus Dorsi Training TRX group: The subjects adjust the weight with 8 ~ 12RM repetitions, with the body directly under the anchor point ( TRX binding and hanging position), with the adduction of the shoulder joint and the contraction of the latissimus dorsi as the main actions, using the feet to support the weight with the help of the ground, the lighter the weight the feet bear with the force, the heavier the weight the feet bear off the ground [5,6].…”
Section: Type Weightmentioning
confidence: 99%
“…2,3 Other applications of the AHG include the treatment of back pain and gym activities to train the core muscles. 1,4,5 The search for an ideal exercise to reinforce the abdominal wall at high activation levels under favorable and safe conditions for the lumbar spine and pelvic diaphragm has encouraged the development of several approaches. [6][7][8] One of the arguments for studying AHG is that it could be a valid training method for the deep abdominal muscles, this could have repercussions in core stability and rehabilitation programs.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,11 Therefore, the present study aimed to investigate how AHG perform against the prone bridge (PB) to determine if they produce higher sEMG signal amplitudes, which are assumed to yield greater strengthening effects. 3,4,12 We hypothesized that AHG will perform better or similarly to the bridge exercise for transversus abdominis/internal oblique (Tra/IO) and external oblique (EO).…”
Section: Introductionmentioning
confidence: 99%